1999
DOI: 10.1074/jbc.274.2.1116
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin Ferroxidase Activity Stimulates Cellular Iron Uptake by a Trivalent Cation-specific Transport Mechanism

Abstract: The balance required to maintain appropriate cellular and tissue iron levels has led to the evolution of multiple mechanisms to precisely regulate iron uptake from transferrin and low molecular weight iron chelates. A role for ceruloplasmin (Cp) in vertebrate iron metabolism is suggested by its potent ferroxidase activity catalyzing conversion of Fe 2؉ to Fe 3؉ , by identification of yeast copper oxidases homologous to Cp that facilitate high affinity iron uptake, and by studies of "aceruloplasminemic" patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 46 publications
1
63
0
2
Order By: Relevance
“…While recent studies in vitro have suggested that ceruloplasmin may function to facilitate non-transferrin-dependent cellular iron influx (15,16), no differences were observed in iron uptake in Cp ϩ/ϩ and Cp Ϫ/Ϫ mice (Table 2), even under experimental conditions designed to favor this uptake pathway when examined over a 72-hr time frame (Fig. 4A).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…While recent studies in vitro have suggested that ceruloplasmin may function to facilitate non-transferrin-dependent cellular iron influx (15,16), no differences were observed in iron uptake in Cp ϩ/ϩ and Cp Ϫ/Ϫ mice (Table 2), even under experimental conditions designed to favor this uptake pathway when examined over a 72-hr time frame (Fig. 4A).…”
Section: Discussionmentioning
confidence: 83%
“…Early studies in copper-deficient animals revealed impaired reticuloendothelial cell iron release that was corrected by the administration of ceruloplasmin, implying a role for this protein as a plasma ferroxidase regulating tissue iron efflux (12)(13)(14). However, such studies were clouded by the effects of copper deficiency in these animals, and more recent work with cultured cell lines in vitro has suggested a role for ceruloplasmin in cellular iron influx (15,16). Understanding how ceruloplasmin affects iron homeostasis is essential for the development of effective therapies in aceruloplasminemia and may provide new insight into the pathogenesis of iron overload.…”
mentioning
confidence: 98%
“…Interestingly, astrocyte Cp is glycosylphosphatidylinositol-linked suggesting that both free and membrane-bound forms of Cp are involved in iron transport processes. Three other laboratories reported that Cp did not increase iron release (even in the presence of apotransferrin) from HepG2 or erythroleukemic K562 cells (19,20), placental BeWo cells (25), or glioblastoma BT325 cells (21).…”
mentioning
confidence: 99%
“…In addition, Cu regulates Fe uptake from low-m.w. complexes in both yeast and some human cells through its role in enzymes with ferrioxidase activity that contribute to Fe acquisition (45,(63)(64)(65). However, we have previously shown that Fe reductase activity in HL-60 cells is not altered by exposure to Ga and other metals and, thus, the ability of the tri/ tetravalent metals to alter cellular Fe acquisition cannot be due to effects on Fe reductase activity (50).…”
Section: Discussionmentioning
confidence: 92%
“…Many cell types have been shown to acquire Fe bound to a variety of low-m.w. chelating agents in vitro (9,12,(43)(44)(45)(46)(47). Several mechanisms have been proposed for this acquisition.…”
mentioning
confidence: 99%